Green engineered cementitious composites with enhanced tensile and flexural properties at elevated temperatures - S. Rawat; C.K. Lee; Y.X. Zhang (Cleaner Materials, 2024)
This study provides new insights in the design of green hybrid polyethylene (PE)-steel fibre reinforced high strength engineered cementitious composite (HSECC) with superior tensile and flexural strength at both ambient and elevated temperatures. Blends of high volume of ground granulated blast furnace slag (GGBFS), dolomite powder and fly ash were utilized to achieve a 60 % cement replacement for the HSECC mixes. These mixes were then exposed to 20–600 °C and a total of 210 specimens were tested to assess their residual tensile stress–strain behaviour, flexural load–displacement response, and toughness. Results indicate that high volume of GGBFS can be very effective in limiting the surface damage and retaining high strength at elevated temperatures. A combination of 1.5 % PE-0.75 % steel with quaternary blend of GGBFS, dolomite and fly ash demonstrated at least 60 % and 40 % retention in tensile and flexural strength at 600 °C, respectively. This was significantly better than the strength of the traditional control silica fume mix considered in this study as well as results reported in many previous literatures on HSECC. Microstructural examination was further conducted to understand the mechanism of fibre deterioration and justify the resulting change in pseudo-hardening behaviour with temperature rise. Findings obtained in this study clearly demonstrated the effectiveness of PE-steel fibre hybridisation at elevated temperature and confirmed that with right binder selection, superior tensile and flexural performance can be achieved even with a very high cement replacement level.